PENGARUH INVESTMENT OPPORTUNITY SET, LIKUIDITAS, DAN PROFITABILITAS TERHADAP KEBIJAKAN DIVIDEN PADA PERUSAHAAN MANUFAKTUR DI MASA PANDEMI COVID-19 - Made Ratih Nurmalasari1; I Made Surya Prayoga (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2022)
The COVID-19 virus that has plagued Indonesia since the beginning of 2020 has had a negative impact on the economy, especially activities in the capital market. In essence, investors are interested in investing by buying company shares because of dividends and capital gains. The dividend policy is taken by the company based on the company's financial information. This study was conducted with the aim of knowing the effect of investment opportunity set, liquidity, and profitability on dividend policy in manufacturing companies listed on the Indonesia Stock Exchange during the COVID-19 pandemic period year of 2020-2021. The population of this study is all manufacturing companies listed on the Indonesia Stock Exchange for the period 2020-2021. The research sample was selected using purposive sampling mcethod. The number of samples in this study were 49 manufacturing companies. This study uses multiple linear regression analysis techniques. The results of this study indicate that the investment opportunity set has no effect on dividend policy, while liquidity and profitability have a significant negative effects on dividend policy.